The Relationship Between Academic Self-Efficacy, Intrinsic Motivation, Coping, Academic Adjustment and Academic Achievement in African International Students - Jaff, Yvette Dufola (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
An increasing number of students travel abroad for higher education and this has led to a growing interest in exploring the factors that influence international students’ academic performance in the host country. This study sought to explore the relationship between academic self-efficacy, coping, academic adjustment and the academic achievement of African international students in North Cyprus. A further aim was to examine the mediation effect of academic self-efficacy between intrinsic motivation and academic performance. A total of 138 students (68 males, 70 females), aged between 18-35 years old (M= 23.08) from African countries such as Nigeria, Cameroon, and Zimbabwe studying at Eastern Mediterranean University completed the Motivated Strategies for Learning Questionnaire, the Proactive Coping Inventory Scale, and the College Adaptation Questionnaire. Results showed that academic self-efficacy was the only significant predictor of academic performance and that academic self-efficacy mediated the relationship between intrinsic motivation and academic performance. These findings suggest that intrinsic motivation can lead to higher academic achievement via positive beliefs about one’s ability to succeed in academic tasks. Keywords: Academic self-efficacy, Intrinsic Motivation, Academic achievement, AfricaninternationalstudentsNorthCyprus.

Öz: Artmakta olan sayılarda öğrenci yüksek öğrenim için yurtdışına seyahat etmektedir, ve bu uluslararası öğrencilerin bulundukları ülkedeki akademik performanslarını etkileyen faktörler konusunda bir ilgi artışına neden olmuştur. Bu çalışma Kuzey Kıbrıs’taki Afrikalı uluslararası öğrencilerde akademik özyeterlik, başa çıkma ve akademik uyum ile akademik başarı arasındaki ilişkiyi araştırmayı hedeflemektedir. Bir başka hedef ise içsel motivasyonun akademik özyeterlik ile akademik performans arasında oynadığı kısmi aracılık rolünü incelemektir. Doğu Akdeniz Üniversitesi’nde öğrenim gören, Nijerya, Kamerun ve Zimbabve gibi Afrika ülkelerinden 18-35 yaşları arasında ve 68 erkek,70 kadın olmak üzere toplam 138 öğrenci (M= 23.08) Güdülenme ve Öğrenme Stratejileri Ölçeği, Proaktif Başa Çıkma Ölçeği ve Üniversite Adaptasyon Ölçeği’ni tamamlamıştır. Sonuçlar akademik performansın kayda değer ölçüde sadece akademik özyeterlik tarafından yordandığını, ayrıca içsel motivasyonun akademik özyeterlik ile akademik performans arasında kısmi aracılık rolü oynadığını göstermiştir. Bu bulgular, uluslararası öğrencilerin becerileri ve akademik kapasiteleriyle ilgili olumlu düşüncelerinin, çalışma motivasyonlarını artırabileceğini ve buna bağlı olarak daha yüksek akademik başarıya neden olabileceğini işaret etmektedir. Anahtar kelimeler: Akademik özyeterlik, akademik başarı, Afrikalı uluslararası öğrenciler,KuzeyKıbrıs.
Master of Science in Developmental Psychology. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Psychology, 2017. Co-Supervisor: Assoc. Prof. Dr. Mehmet Erginel, Supervisor: Assist. Prof. Dr. İlmiye Seçer.
Keywords: Psychology; Developmental Psychology; African Students; Academic achievement; Cyprus, North; Educational Psychology; Academic Self Efficacy; Intrinsic Motivation; Academic Achievement; African International Students; North Cyprus